The rise of the English shipping industry in the seventeenth and eighteenth centuries - Davis, Ralph, 1915- (Research in maritime history, 2012)
This volume is a reprint of Ralph Davis' seminal 1962 book, The Rise of the English Shipping Industry in the Seventeenth and Eighteenth Centuries. The aim was to examine the economic reasons for the growth of British shipping before the arrival of modern technology, with a particular attention on overseas trade. The study can roughly be divided into two halves. The first is an in-depth exploration the roles within the shipping industry, from shipbuilders and shipowners to seamen and masters, from an economic perspective. The second is a chapter-by-chapter review of British overseas trade with Northern Europe, Southern Europe, the Mediterranean, East India, and America and the West Indies. The final two chapters diverge from the main sections, and focus on the interplay between government, war, and shipping. Davis attaches no extra significance to any particular nation or role, and offers an even-handed approach to maritime history still considered rare in the present day. Costs, profits, voyage estimates, ship-prices, and earnings all come under close and equal scrutiny as Davis seeks to understand the trades and developments in shipping during the period. To conclude, he places the study into a broader historical context and discovers that shipping played a measured but crucial role in the development of industrialisation and English economic development. This edition includes an introduction by the series editor; Davis' introduction and preface; seventeen analytical chapters; a concluding chapter; two appendices concerning shipping statistics and sources; and a comprehensive index.